The Sraffian supermultiplier and cycles: Theory and empirics - Michalis Nikiforos; Marcio Santetti; Rudiger Von Arnim (Levy Economics Institute of Bard College, 2021)
This paper provides a theoretical and empirical reassessment of supermultiplier theory. First, we show that, as a result of the passive role it assigns to investment, the Sraffian supermultiplier (SSM) predicts that the rate of utilization leads the investment share in a dampened cycle or, equivalently, that a convergent cyclical motion in the utilization-investment share plane would be counterclockwise. Second, impulse response functions from standard recursive vector autoregressions (VAR) for postwar US samples strongly indicate that the investment share leads the rate of utilization, or that these cycles are clockwise. These results raise questions about the key mechanism underlying supermultiplier theory.
Keywords: E12; E24; E25; E32; 330; Sraffian Supermultiplier; Cyclical Growth; (Induced) Investment; Desired Rate of Capacity Utilization